Eğin [Kemaliye] and Ilic Bridges of Erzincan from the Ottoman Empire to the Rebuplic - Çakar, Enver; Şen, Korkmaz; Kısa, Yavuz; Toprak, Ahmet; Olgun, Tuba N.; Şahin, Murat (Selim Hilmi Ozkan, 2025)
The historical road network from Diyarbakir stretched to Erzincan via Harput-Eğin (Kemaliye)Ilic reached Iran and the Black Sea. However, the Euphrates River was disrupting this transportation network in some places. A bridge was built in two separate areas to provide direct transportation on this road, which was very important in military and commercial terms during the Ottoman and Republican periods. Although the construction date of the bridge in Eğin is unknown, its existence can be traced back to the middle of the 17th century. The bridge in Ilic was built in the last quarter of the 19th century. Both bridges, renewed during the Republican Period, were under the Keban Dam Lake, so new ones were built. Therefore, the main subject of the study is the historical bridges built over the Euphrates River in Eğin and Ilic, and the time interval is the period from the 17th century to the present day, when the first determinations about the bridges were made. The study's primary purpose is to explain the importance of these bridges in Anatolian transportation networks and architectural history. © 2025, Selim Hilmi Ozkan. All rights reserved.
Osmanlı’dan Cumhuriyet’e Erzincan’ın Eğin [Kemaliye] ve İliç Köprüleri
Keywords: Erzincan; Eğin; Historical Bridges; Ilic; Kemaliye